Evaluation of sulfonated chitosan-g-sulfonated polyvinyl alcohol/polyethylene oxide/sulfated zirconia composite polyelectrolyte membranes for direct borohydride fuel cells: Solution casting against the electrospun membrane fabrication technique - Gouda, Marwa H.; Elessawy, Noha A.; Elnouby, Mohamed; Ghorab, Mohamed A.; Radwan, Islam Othman; Hashim, Ali; Youssef, M. Elsayed; Santos, Diogo M. F. (Frontiers in Materials, 2022)
Sulfonated chitosan-g-sulfonated polyvinyl alcohol/polyethylene oxide doped with sulfated zirconia composite polyelectrolyte membranes (SCS-g-SPVA/PEO/SZrO2) have been developed for direct borohydride fuel cell applications. Two fabrication techniques have been used to prepare the membranes: solution casting and electrospun, to have the membranes in film and fiber forms. For the casting technique, different concentrations of SZrO2 (1-3 wt.%) were used, while the optimum concentration of SZrO2 (3 wt.%) was used in the electrospun one (SCS-g-SPVA/PEO/SZrO2-CF). The SCS-g-SPVA/PEO/SZrO2-C membranes were prepared in a single step. The grafting and the crosslinking were done using glutaraldehyde and sulfosuccinic acid as sulfonating agents for CS and PVA and coupling agents simultaneously using click chemistry. On the other hand, the SCS-g-SPVA/PEO/SZrO2-CF membranes were prepared in two steps. They were fabricated with electrospinning and then dipped into the coupling and crosslinking solutions. The two types of membranes were characterized using FTIR, DSC, and TGA. The study revealed that the casting membranes’ physicochemical properties were improved by increasing the SZrO2 content. In addition, it was found a reduction in borohydride permeability as SZrO2 increased.